Efficacy and safety of robotic-assisted versus endoscopic-assisted axillary lymph node dissection in node-positive breast cancer: a retrospective comparative study - Zhijie Wu; Qiwen Liu; Zongyan Li; Zuxiao Chen; Yongxin Wu; Yunxiang Luo; Lina Wei; Qiongyu Hu; Haiyan Li (World Journal of Surgical Oncology)
Abstract Background Robotic surgery is increasingly being adopted for breast cancer treatment. However, robust clinical evidence regarding its effectiveness and safety remains limited. This retrospective cohort study aimed to compare the surgical quality and short-term outcomes of robotic-assisted axillary lymph node dissection (R-ALND) and endoscopic-assisted axillary lymph node dissection (E-ALND) in patients with node-positive breast cancer. Here, we report the short-term outcomes of this trial. Methods This single-center retrospective study compared the short-term efficacy and safety of R-ALND and E-ALND in patients with node-positive breast cancer. Patients who underwent surgery at the Sixth Affiliated Hospital of Sun Yat-sen University between January 2022 and October 2024 were included. Clinical and pathological characteristics, surgical outcomes, and postoperative complications were analyzed. Results A total of 56 patients were included, with 29 undergoing E-ALND and 27 undergoing R-ALND. The R-ALND group demonstrated significantly shorter operative times (43.37 ± 12.40 min vs. 60.10 ± 19.37 min, p < 0.001) and lower mean intraoperative blood loss (3.26 ± 2.40 ml vs. 9.24 ± 4.29 ml, p < 0.001). Postoperatively, the R-ALND group exhibited better upper limb function and sensation, as evidenced by significantly lower DASH scores at 1-month (10.87 ± 1.35 vs. 14.64 ± 3.49, p < 0.001) and 3-month (6.68 ± 1.86 vs. 9.24 ± 2.74, p < 0.001) follow-ups. Additionally, the R-ALND group had fewer postoperative complications, including a reduced incidence of sensory disturbances, burning sensations, and numbness in the upper limb. Conclusion Compared with E-ALND, R-ALND significantly reduces intraoperative blood loss and postoperative complications, with less impact on upper limb function and sensory outcomes. These findings indicate that R-ALND may provide better clinical benefits for patients requiring axillary lymph node dissection in the management of breast cancer.